PAHLAWANKU TELADANKU: PENGUATAN KARAKTER DAN ETIKA MENUJU GENERASI MUDA TANGGUH - Ristati Marpaung; Roli Yanti Laoli; Rosmelina Naibaho; Rumiris Taruli Pardede; Tessa Lonika Hutagalung (Pusat Riset dan Inovasi Nasional, 2022)
This research is motivated by a problem that we often see, namely that Christian youth with character and ethics are very difficult for us to meet in our lives today. It takes an education to make a young man of character and ethics. The purpose of this paper is to know how to become a Christian youth of good character and ethics in accordance with the will and righteousness of Christ. The method used is a literature study approach. The author collected data from a number of literature related to the discussion of being a Christian youth with character and ethics. Christian character is the qualities embodied in Christian teachings that Christians should exemplify by looking at the character of Christ. The character of Christ is a character that Christian youth should have. Ethical Christian youth are young men whose behavior follows the teachings of Christ, has morals based on the Bible. Able to be a good young Christian, who does the right things, the things that Christ desires. It is not easy to become a Christian youth with character and ethics but presumably through this writing it can motivate and change the thoughts and behaviors of Christian youth to become young men of character and ethics. A Christian youth who is ethical and characterful is a young man who reflects his true life. Therefore, we raised the title